2018
DOI: 10.1093/pubmed/fdy047
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the shift work experience: the perceived effect on eating habits, lifestyle behaviours and psychosocial wellbeing

Abstract: Shift work affects many areas of workers' lives, negatively impacting on eating and lifestyle behaviours and psychosocial health. This study augments the current literature as it highlights the role internal motivation plays in workers' lifestyle choices. The research should help inform the development of public health strategies to minimize the impact of shift work, such as specialist behavioural change interventions specific to this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
25
0
4
Order By: Relevance
“…In addition, findings showed that poorer mood was associated with a higher intake of fat and saturated fat which concurs with prior studies (18). It is possible that the nurses in the current study were using food as a coping strategy for dealing with negative mood states (36,37). Investigating ways to improve the mood of shift workers may in turn assist with reduced consumption of food and healthier food choices.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, findings showed that poorer mood was associated with a higher intake of fat and saturated fat which concurs with prior studies (18). It is possible that the nurses in the current study were using food as a coping strategy for dealing with negative mood states (36,37). Investigating ways to improve the mood of shift workers may in turn assist with reduced consumption of food and healthier food choices.…”
Section: Discussionsupporting
confidence: 88%
“…In the past decade, many studies have documented the negative impacts from shift work on biological homeostasis and circadian rhythm, which can in turn lead to sleep disturbances (Boivin & Boudreau, ; Nea et al, ). Sleep disturbances can trigger the stress response, with subsequent activation of inflammatory pathways, and can result in adverse health outcomes and behavioural problems (Irwin, Olmstead, & Carroll, ), and increased risk of sleepiness‐related accidents and injuries in the workplace (Fafrowicz et al, ; Weaver, Stutzman, Supnet, & Olson, ).…”
Section: Introductionmentioning
confidence: 99%
“…11 The limited published data on the experience of Irish shift workers have demonstrated that shift work may negatively affect their health behaviours and psychosocial well-being. 12 Factors relating to the work environment have been identified which may act as barriers or facilitators in their effect on the ability of Irish shift workers to maintain healthy lifestyle behaviours both at work and at home. Further evidence-based insights of this nature are required to inform the development of public and occupational health measures to optimise the health and health behaviours of shift workers.…”
Section: Bmj Nutrition Prevention and Healthmentioning
confidence: 99%